2021
DOI: 10.3390/plants10112255
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Diversity of Morphological Characteristics of Pitahaya (Selenicereus Megalanthus Haw.) Germplasm in Colombia

Abstract: Yellow pitahaya is an exotic fruit that is rich in essential nutrients and antioxidants. In Colombia, it grows naturally in warm areas, but it is not clear which species exist because this genus presents a lot of intra and interspecific hybridization. More studies are needed in this field along with characterizations of the genotypes. This study aimed to undertake an in situ morphoagronomic evaluation of yellow pitahaya genotypes from five municipalities in Boyacá, Colombia. Measurements were taken in a comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In this study, the genotypes showed the shape of margin between areolas between concave and right, contrary to that reported in other studies on different species of Hylocereus, where the predominant forms were convex, with the presence of wax (Abirami et al, 2021). The cladode width and distance between areoles corresponded well with earlier studies from México (Castillo et al, 2005), India (Abirami et al, 2021), Puerto Rico and Colombia (Morillo et al, 2021;Betancur et al, 2020;Goenaga et al, 2020).…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…In this study, the genotypes showed the shape of margin between areolas between concave and right, contrary to that reported in other studies on different species of Hylocereus, where the predominant forms were convex, with the presence of wax (Abirami et al, 2021). The cladode width and distance between areoles corresponded well with earlier studies from México (Castillo et al, 2005), India (Abirami et al, 2021), Puerto Rico and Colombia (Morillo et al, 2021;Betancur et al, 2020;Goenaga et al, 2020).…”
Section: Discussionsupporting
confidence: 50%
“…Fifteen yellow pitahaya genotypes were evaluated, which were selected in an in situ morphoagronomic characterization study carried out in the main producing municipalities of the Lengupá province: Berbeo, Zetaquira, Paéz, San Eduardo and Miraflores (Morillo et al, 2021). The 15 genotypes were established in two experimental plots in the municipalities of Miraflores and Zetaquira under two production systems in the open field (8 genotypes) and under cover (7 genotypes), the experimental design was completely randomized, with 10 repetitions per genotype and in where the treatments corresponded to the 15 selected yellow pitahaya genotypes (Table 1, Figure 1).…”
Section: Vegetal Materialsmentioning
confidence: 99%
See 3 more Smart Citations